Method for green preparation of high-purity ammonium paratungstate from tungsten ore
By employing green ammoniacal decomposition, functionalized phosphate ester-based ionic liquid extraction, and ultrasonic-assisted cooling crystallization technologies, combined with mother liquor recycling, the problems of high pollution, high energy consumption, and resource waste in tungsten smelting have been solved, achieving low-energy and green preparation of high-purity ammonium paratungstate.
Patent Information
- Application Number
- CN202511397435.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2025-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing tungsten smelting technologies suffer from high pollution, high energy consumption, insufficient product purity, and resource waste, making it difficult to achieve green production and resource recycling.
By employing green ammonia decomposition, functionalized phosphate ester-based ionic liquid extraction, and ultrasonic-assisted cooling crystallization technologies, combined with mother liquor recycling, a fully alkaline system is formed to achieve low-pollution, low-energy consumption, and high-purity preparation of high-purity ammonium paratungstate through tungsten ore decomposition, purification, and crystallization.
The preparation of high-purity ammonium paratungstate with a product purity of ≥99.995% has been achieved, reducing energy consumption and environmental impact, improving process stability and resource utilization, and meeting the requirements of green production.
Smart Images

Figure CN121158831A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of tungsten smelting, and particularly relates to a method for green preparation of high-purity ammonium paratungstate from tungsten ore. BACKGROUND
[0002] Ammonium paratungstate (APT) is a key intermediate for the preparation of metallic tungsten, hard alloy and high-end tungsten-based materials. Its preparation process has long relied on traditional tungsten ore decomposition, solution purification and crystallization technology. In the prior art, sodium hydroxide strong alkali dissolution or high-temperature roasting (such as soda roasting and calcification roasting) process is usually used for tungsten ore decomposition. The former needs to consume a large amount of strong corrosive alkali liquor, and the alkali source cannot be recycled, resulting in high production cost and serious equipment corrosion. The latter has problems of high energy consumption and roasting waste gas pollution. Traditional extractants such as tributyl phosphate (TBP) are generally used for solution purification, which can separate tungsten and impurities, but has poor selectivity for trace impurities such as phosphorus, arsenic and silicon, and is easy to cause co-extraction, affecting the purity of the product. In addition, TBP is volatile, and there is a risk of organic pollutant emission. The crystallization process usually uses evaporation crystallization to improve the supersaturation of the solution by heating and dehydration, which not only has high energy consumption, but also has uneven crystal growth rate, and is easy to cause agglomeration, affecting the particle size distribution of the product. In addition, the treatment of crystallization mother liquor and washing wastewater in the existing process is mainly end-of-pipe treatment, and the resource recycling rate of ammonia nitrogen and other resources is low, resulting in waste of water resources and environmental pollution, which cannot meet the green production requirements.
[0003] The above prior art has the following significant deficiencies in practical application: first, the traditional decomposition and mother liquor treatment process lacks resource recycling design, and the problems of high pollution and resource waste caused by strong alkali or roasting are prominent, which cannot realize the green production goal of "source pollution reduction-resource recycling"; second, the selectivity of extractants and the crystallization regulation ability are limited, which makes it difficult to break through 99.99% in product purity, and the crystal uniformity is poor, which affects the downstream application; third, the existence of high-energy consumption units such as roasting and evaporation makes the whole process energy consumption high, which does not meet the energy saving and consumption reduction trend of the industry; fourth, the corrosion of strong alkali system to the equipment and the influence of process parameter fluctuation on the stability further limit the production efficiency and cost control. Therefore, it is a technical problem to be solved in the current tungsten smelting field to develop a green preparation method of high-purity ammonium paratungstate with low pollution, high purity, low energy consumption and process stability. SUMMARY
[0004] In view of the above-mentioned deficiencies of the prior art, the purpose of the present application is to provide a method for green preparation of high-purity ammonium paratungstate from tungsten ore, so as to solve one or more problems in the prior art.
[0005] To achieve the above-mentioned purpose, the technical scheme of the present application is as follows:
[0006] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0007] (1) Tungsten ore pretreatment: crush and grind the tungsten ore to -200 mesh, with a proportion of ≥90%.
[0008] (2) Green ammonia decomposition: mix and react the pretreated tungsten ore with a leaching agent, the leaching agent is composed of 10-12 parts of ammonium carbonate, 5-8 parts of ammonia water and 70-80 parts of deionized water, the reaction temperature is 60-80℃, the stirring rate is 300-500r / min, the reaction time is 2-4h, and the liquid-solid ratio is 4:1-6:1 mL / g.
[0009] (3) Deep purification of ionic liquid: extract the crude tungsten acid ammonium solution of step (2) with functionalized phosphate-based ionic liquid, the concentration of functionalized phosphate-based ionic liquid is 0.5-1.0 mol / L, the extraction phase ratio O / A is 1:3-1:5, and the temperature is 25-30℃.
[0010] (4) Ultrasonic-assisted cooling crystallization: cool and crystallize the tungsten acid ammonium solution after extraction under ultrasonic field, the ultrasonic frequency is 20-30 kHz, the power is 300-500 W, the cooling rate is 5-8℃ / h, and the final temperature is 20-25℃.
[0011] (5) Mother liquor recycling: the crystallization mother liquor is subjected to ammonia evaporation under reduced pressure, carbonization reaction and tungsten residue recovery, the ammonia evaporation vacuum degree is 0.08-0.09 MPa, the temperature is 60-70℃, and the CO2 flow rate for carbonization reaction is 0.5-1.0 L / min.
[0012] (6) Drying of ammonium paratungstate: dry the crystallization product at 80-100℃, vacuum degree 0.07-0.08 MPa for 2-3h.
[0013] Specifically, the tungsten ore in step (1) is scheelite or wolframite concentrate with WO3 grade ≥65%. The crushing is carried out by using a jaw crusher, and the particle size after crushing is ≤3mm. The grinding is carried out by using a ball mill, the rotating speed is 300-350r / min, the medium ball diameter is Φ20-30mm, the ball-to-material ratio is 5:1, the grinding time is 1.5-2h, and the screening is carried out by using a 200 mesh standard screen, with the oversize returned to the ball mill.
[0014] Specifically, the pH of the green ammonia decomposition in step (2) is controlled at 9.5-10.5, and the reaction equipment is a enamel reaction kettle. After the reaction, the solid-liquid separation is carried out by using a plate and frame filter, the filter cloth aperture is 0.45μm, the filter residue is calcium carbonate or iron-manganese carbonate and is sent to tailings recovery, and the filtrate is a crude tungsten acid ammonium solution with WO3 concentration of 80-120g / L.
[0015] Specifically, the functionalized phosphate ionic liquid in step (3) is 1-octyl-3-methyl imidazole diethyl phosphate salt, and the diluent is sulfonated kerosene. The stirring rate in the extraction process is 200-300 r / min, the mixing time is 15-20 min, and the clarification time is 30-40 min. After the ionic liquid is extracted and stripped for 50 times, the extraction capacity decreases by no more than 3%.
[0016] Further, step (3) further comprises washing and stripping: the washing agent is an ammonium carbonate solution with a concentration of 0.5-1.0 wt%, and the phase ratio O / A is 5:1-10:1. The stripping agent is an ammonia solution with a concentration of 1-2 wt%, and the phase ratio O / A is 1:1, and the stripping time is 20-25 min.
[0017] Specifically, before the ultrasonic-assisted cooling crystallization in step (4), the ammonium tungstate solution is subjected to 0.22 μm precision filtration. In the crystallization process, nanoscale ammonium paratungstate seeds are added, and the addition amount is 0.5-1.0 wt% of the mass of WO3 in the solution, the stirring rate is 200-300 r / min, and the crystallization time is 4-6 h. The ultrasonic is in intermittent mode, which is turned on for 5 min, turned off for 5 min, and turned on for 5 min in a cycle.
[0018] Specifically, after the crystallization in step (4), the solid-liquid separation is carried out by centrifugal filtration at a speed of 3000-4000 r / min for 15-20 min. The filter cake is washed with deionized water for 2-3 times, and the washing water is reused as the water for the leaching agent in step (2).
[0019] Specifically, after the ammonia evaporation in step (5), the ammonia gas is condensed to obtain an ammonia water with a concentration of 15-20 wt%, which is returned to step (2) as the leaching agent; the carbonization reaction temperature is 30-40℃, the pressure is 0.2-0.3 MPa, the reaction time is 2-3 h, and an ammonium carbonate solution with a concentration of 10-12 wt% is generated and returned to step (2) as the leaching agent.
[0020] Specifically, in step (5), the tungsten residue is recovered by using D401 chelating resin. The flow rate of the residual liquid is 1-2 BV / h, and the breakthrough point is controlled to be greater than 0.1 g / L of WO3 in the effluent. The eluent is an ammonia solution with a concentration of 2-3 wt%, and the flow rate is 0.5-1 BV / h. The eluate is returned to step (3) for extraction.
[0021] Specifically, in step (6), the ammonium paratungstate is dried by segment drying: drying at 60℃ for 0.5-1 h, drying at 80℃ for 0.5-1 h, and drying at 100℃ for 0.5-1 h. After drying, nitrogen is introduced to cool to room temperature. The product has a moisture content of ≤0.5%, and the crystal particle size D50 is 30-50 μm.
[0022] Compared with the prior art, the present application has the following beneficial technical effects:
[0023] (I) Through the combination of the weak alkaline ammonium carbonate-ammonia system of the green ammonia decomposition unit and the ammonia-carbon recycling mechanism of the mother liquor recycling unit, low pollution and resource efficient recycling of the tungsten ore decomposition process are realized. The green ammonia decomposition uses a weak alkaline system to replace the traditional strong alkali or roasting process, reducing the use of strong corrosive substances and high energy consumption from the source; the mother liquor recycling reuses the decomposition agent ammonia and ammonium carbonate to the decomposition unit through ammonia evaporation-carbonation reaction, forming a closed loop of "decomposition-recovery-redecomposition", avoiding the waste of resources and ammonia nitrogen emissions caused by the one-time consumption of alkali source in the traditional process, and significantly reducing the environmental load of the whole process.
[0024] (II) Through the combination of the functionalized phosphate-based ionic liquid extraction of the ionic liquid deep purification unit and the ultrasonic field regulation crystallization mechanism of the ultrasonic assisted cooling crystallization unit, the purity and crystal quality of ammonium paratungstate product are synergistically improved. The functionalized ionic liquid has stronger selective complexing ability due to its specific phosphate-based active groups, which can deeply remove trace impurities such as phosphorus, arsenic, and silicon; ultrasonic assisted cooling crystallization destroys the supersaturation state and promotes crystal directional growth through cavitation effect, reducing crystal agglomeration. The combination of the two breaks through the bottleneck of traditional process in product purity, and optimizes the crystal size distribution, solving the problems of insufficient purity and poor crystal uniformity in existing technology.
[0025] (III) Through the combination of the green ammonia decomposition unit which omits the roasting step, the ultrasonic assisted cooling crystallization unit which replaces the evaporation crystallization process, and the mother liquor recycling unit which reduces raw material consumption, low energy consumption and process sustainability of the whole process are realized. The green ammonia decomposition directly completes the decomposition of tungsten ore in solution, omitting the high-temperature energy consumption of traditional roasting; the ultrasonic assisted cooling crystallization replaces heating evaporation dehydration with physical field regulation, significantly reducing the crystallization energy consumption; the mother liquor recycling reduces the demand for purchased ammonia and ammonium carbonate, reducing raw material cost. The synergistic effect of the three makes the total energy consumption of the process significantly lower than that of existing technology, and improves the long-term sustainable operation ability of the process through resource recycling.
[0026] (IV) Through the combination of the weak alkaline system of the green ammonia decomposition unit and the whole process closed loop design, the process stability and equipment friendliness are improved. The green ammonia decomposition uses a weak alkaline ammonium carbonate-ammonia system, avoiding the strong corrosion of traditional strong alkali process to the equipment, prolonging the service life of the equipment; the whole process closed loop design (mother liquor recycling, washing water reuse) reduces the introduction of external impurities, reducing the process fluctuation risk. The combination of the two makes the process maintain stable tungsten leaching rate and product quality in long-term operation, reduces equipment maintenance cost, and solves the problems of serious equipment corrosion and poor process stability in existing technology. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 is a flowchart of the method in the present application. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present application more clear, the present application is further described in detail below in combination with the drawings and exemplary description. It should be noted that the structure, proportion, size, etc. shown in the drawings of the present specification are only used to cooperate with the content disclosed in the present specification for understanding and reading by those skilled in the art, and are not used to limit the implementation conditions of the present application, so they do not have technical substantive significance. Any modification of structure, change of proportion relationship or adjustment of size, without affecting the effects and purposes that can be achieved by the present application, should still fall within the scope covered by the disclosed technology.
[0029] Summary of the application
[0030] In the field of ammonium paratungstate (APT) preparation, the industry has long used conventional process schemes for core technical problems such as tungsten ore decomposition, solution purification, crystallization, and mother liquor treatment. Specifically, the tungsten ore decomposition stage relies on sodium hydroxide strong alkali dissolution or high-temperature roasting (such as soda roasting, calcification roasting) process to dissolve tungsten elements by destroying the tungsten ore lattice in a strong alkali environment or high-temperature oxidation. Traditional organic extractants such as tri-butyl phosphate (TBP) are commonly used in the solution purification stage to separate impurities by utilizing the complexation of their phosphate groups with tungstate ions. The crystallization process mainly uses evaporation crystallization technology to promote APT crystal precipitation by increasing the solution supersaturation through solvent evaporation. End-of-pipe treatment is mainly used for mother liquor and wastewater treatment to reduce pollutant emissions through neutralization and precipitation, and the resource recovery rate of ammonia nitrogen and tungsten is low.
[0031] However, the above conventional schemes have significant shortcomings: first, the strong alkali dissolution or high-temperature roasting process has high pollution and high energy consumption problems. The use of strong alkali leads to severe equipment corrosion and the inability to recycle the alkali source, and the roasting process is accompanied by large amounts of waste gas emissions and energy consumption. Second, the selectivity of traditional extractants is limited, and the co-extraction rate of trace impurities such as phosphorus, arsenic, and silicon is high, making it difficult to meet the stringent requirements of high-purity APT for impurity content. Organic extractants are volatile and pose an environmental risk. Third, evaporation crystallization relies on heating to remove water, which has a high energy consumption proportion, and the crystal growth rate is uneven, which can lead to agglomeration and affect the uniformity of product particle size distribution. Fourth, the lack of resource recovery of mother liquor leads to the emission of pollutants such as ammonia nitrogen and the waste of tungsten resources, which does not meet the industry trend of green production and resource recycling. These defects collectively restrict the sustainable development and product quality improvement of APT preparation technology.
[0032] Comprehensive description
[0033] A method for green preparation of high-purity ammonium paratungstate from tungsten ore
[0034] I. Process overview
[0035] The present application aims to solve the problems of serious pollution, high energy consumption, insufficient product purity and resource waste in traditional process by the synergistic application of weak alkaline decomposition, functional extraction, low energy consumption crystallization and resource recycling technology. The method comprises six continuous units of tungsten ore pretreatment, green ammonia decomposition, ionic liquid deep purification, ultrasonic assisted cooling crystallization, mother liquor recycling and ammonium paratungstate drying, and the whole process uses a weak alkaline system to realize ammonia nitrogen resource closed loop and zero wastewater discharge, and finally obtain ammonium paratungstate products with purity ≥99.995%.
[0036] II. Specific process steps
[0037] (I) Tungsten ore pretreatment
[0038] First, the tungsten ore raw material is pretreated to improve the subsequent decomposition efficiency. The tungsten ore is scheelite or wolframite concentrate, wherein the WO3 grade is ≥65%. The pretreatment process includes crushing, grinding and screening in turn: the crushing adopts a jaw crusher to crush the tungsten ore to a particle size of ≤3mm; the grinding adopts a ball mill, the ball mill speed is controlled at 300-350r / min, the medium ball diameter is Φ20-30mm, the ball to material ratio is 5:1, and the grinding time is 1.5-2h, so that the particle size of the ore powder reaches ≥90% of -200 mesh; the screening uses a 200 mesh standard screen, the undersize is fed into the subsequent decomposition process, and the oversize is returned to the ball mill for regrinding.
[0039] (II) Green ammonia decomposition
[0040] The pretreated tungsten ore powder is mixed with a leaching agent at a liquid to solid ratio of 4:1-6:1 mL / g, and the green ammonia decomposition reaction is carried out in a enamel reaction kettle. The leaching agent is composed of 10-12 parts of ammonium carbonate, 5-8 parts of ammonia water and 70-80 parts of deionized water by mass fraction, which destroys the tungsten ore lattice and dissolves the tungsten element through a weak alkaline system. During the reaction, the temperature is controlled at 60-80℃, the stirring speed is 300-500r / min, the reaction time is 2-4h, and the system pH is adjusted to 9.5-10.5 by ammonia water to avoid ammonia gas escape and equipment corrosion. After the reaction, solid-liquid separation is carried out by plate and frame filtration, the filter cloth aperture is 0.45μm, the filter residue is mainly calcium carbonate or iron manganese carbonate, which is sent to the tailings recovery process; the filtrate is a crude tungsten acid ammonium solution, wherein the WO3 concentration is controlled at 80-120g / L, which is fed into the subsequent purification process.
[0041] (III) Ionic liquid deep purification
[0042] The functionalized phosphate group ionic liquid is used to purify the crude ammonium tungstate solution to remove the trace impurities such as phosphorus, arsenic and silicon. The ionic liquid is 1-octyl-3-methyl imidazole diethyl phosphate salt, which is dissolved in sulfonated kerosene to prepare the organic phase with the ionic liquid concentration of 0.5-1.0 mol / L. The extraction process is carried out in a mixed clarifier, and the three-stage extraction, two-stage stripping and one-stage washing process is adopted. The phase ratio O / A is 1:3-1:5 in the extraction section, the temperature is 25-30℃, the stirring speed is 200-300 r / min, the mixing time is 15-20 min, and the clarification time is 30-40 min. The ammonium carbonate solution with the concentration of 0.5-1.0 wt% is used as the washing agent in the washing section with the phase ratio O / A of 5:1-10:1 to remove the water phase impurities entrained in the organic phase. The ammonia solution with the concentration of 1-2 wt% is used as the stripping agent in the stripping section with the phase ratio O / A of 1:1, and the stripping time is 20-25 min, so that the loaded water phase with the WO3 concentration of 150-180 g / L is obtained, and the impurities P, As and Si have the content of ≤0.1 g / L. After the stripping, the ionic liquid is dried in vacuum (60℃, 0.08 MPa) to remove the residual water, and then is recycled. After 50 times of extraction and stripping cycles, the extraction capacity decreases by ≤3%.
[0043] (IV) Ultrasonic-assisted cooling crystallization
[0044] After the purified ammonium tungstate solution is filtered through a 0.22 μm precision filter, it is sent to a jacketed crystallizer for ultrasonic-assisted cooling crystallization. During the crystallization process, nanoscale ammonium paratungstate seeds with a particle size of 5-10 μm and a purity of ≥99.999% are added in an amount of 0.5-1.0 wt% (based on the WO3 mass in the solution), and the stirring speed is controlled at 200-300 r / min (anchor stirring) to avoid the settlement of the crystals. At the same time, an ultrasonic device is turned on, the ultrasonic frequency is 20-30 kHz, the power is 300-500 W, and the intermittent ultrasonic mode (5 min on, 5 min off, 5 min on in a cycle) is adopted to promote the nucleation and growth of the crystals. The crystallization temperature is controlled by programmed cooling, the initial temperature is 60-70℃, the cooling rate is 5-8℃ / h, the final temperature is reduced to 20-25℃, and the total crystallization time is 4-6 h (including cooling and incubation). After the crystallization is completed, the solid-liquid separation is carried out by centrifugal filtration, the centrifugal speed is 3000-4000 r / min, and the centrifugal time is 15-20 min. The filter cake is washed with deionized water for 2-3 times to remove the free ammonium ions on the surface, and the washing water is recycled to the green ammonia decomposition process as the leaching agent.
[0045] (V) Mother liquor recycling
[0046] The centrifugal filtration of the crystalline mother liquor (containing (NH4)2WO45-10 g / L, NH3H2O 3-5 wt%) is sent to the mother liquor recycling system, and is sequentially subjected to vacuum ammonia evaporation, carbonization reaction and tungsten residue recovery. The vacuum ammonia evaporation is performed in a vacuum distillation column, the vacuum degree is controlled to be 0.08-0.09 MPa, the temperature is controlled to be 60-70 °C, the distillation time is controlled to be 2-3 h, the ammonia gas evaporated is condensed to obtain ammonia water with a concentration of 15-20 wt%, and is returned to the green ammonia decomposition process as a leaching agent; the residue at the bottom of the distillation column (containing WO30.5-1.0 g / L) is sent to the tungsten residue recovery process, and is adsorbed by using D401 type chelating resin (amino phosphonic acid group, adsorption capacity 50-60 mg WO3 / g resin), the flow rate of the residue is 1-2 BV / h (BV is the volume of the resin column), and the breakthrough point is controlled to be WO3 concentration in the effluent >0.1 g / L; after adsorption saturation, 2-3 wt% ammonia water solution is used as an eluent, the elution flow rate is 0.5-1 BV / h, and the eluate is returned to the ionic liquid deep purification process for extraction. The carbon dioxide gas generated in the ammonia evaporation process is introduced into the carbonization reaction kettle, and reacts with deionized water at a temperature of 30-40 °C and a pressure of 0.2-0.3 MPa for 2-3 h to generate an ammonium carbonate solution with a concentration of 10-12 wt%, which is returned to the green ammonia decomposition process as a leaching agent.
[0047] (VI) Drying of ammonium paratungstate
[0048] The ammonium paratungstate wet crystals obtained by centrifugal filtration are sent to a vacuum drying oven for drying. The drying process adopts staged temperature control: first drying at 60 °C for 0.5-1 h, then increasing the temperature to 80 °C for drying for 0.5-1 h, and finally increasing the temperature to 100 °C for drying for 0.5-1 h, and the total drying time is 2-3 h. The vacuum degree is controlled to be 0.07-0.08 MPa during the drying process, so as to reduce the drying temperature and avoid oxidation of the crystals. After drying is completed, nitrogen is introduced to cool to room temperature (to avoid moisture absorption), and ammonium paratungstate product is obtained, the product moisture content is ≤0.5%, the crystal particle size D50 is 30-50 μm, and the purity is ≥99.995% (impurity content: Na ≤5 ppm, Fe ≤3 ppm, Si ≤2 ppm).
[0049] In order to verify the influence of the key process parameters in the process on the performance of the ammonium paratungstate product and clarify the actual significance of the parameter range, the following comparative experiments are designed by controlling variables to verify the core parameters of the green ammonia decomposition, ionic liquid purification and ultrasonic crystallization links, and the product performance is tested by combining the national standard method.
[0050] I. Experimental design
[0051] (I) Test standard
[0052] Purity of Ammonium Paratungstate: According to GB / T 10574.2-2003 "Chemical analysis method of ammonium paratungstate - Determination of loss on ignition by gravimetric method" and inductively coupled plasma mass spectrometry (ICP-MS) to determine the impurity content, purity = 100% - ∑impurity content (Na, Fe, Si, P, As, etc.).
[0053] Crystal particle size D50: According to ISO 13320-1:2009 "Particle size analysis - Laser diffraction methods", using a laser particle size analyzer (Malvern Mastersizer 3000) for testing.
[0054] Moisture content: According to GB / T 6284-2016 "General method for determination of moisture in chemical products - Gravimetric method", drying to constant weight in a 105°C oven, and calculating the moisture content.
[0055] (II) Variable selection
[0056] Three key process parameters that significantly affect product performance were selected as variables, with specific ranges as follows:
[0057] Variable A: mass fraction of ammonium carbonate in green ammonia decomposition, preset limited range 10-12;
[0058] Variable B: ionic liquid concentration (mol / L) in ionic liquid deep purification, preset limited range 0.5-1.0 mol / L;
[0059] Variable C: ultrasonic power (W) in ultrasonic-assisted cooling crystallization, preset limited range 300-500 W.
[0060] (III) Experimental group setting
[0061] A total of 10 groups of experiments were designed, with the remaining process parameters (such as 5-8 parts of ammonia water, liquid-solid ratio 4:1-6:1, cooling rate 5-8 ℃ / h, etc.) kept consistent. Grouping is as follows:
[0062] Conventional group (1-5 group): variables A, B, and C are within the preset required limited range;
[0063] Exceeding control group (6-9 group): variable A, B, or C exceeds the preset limited range (lower than the lower limit or higher than the upper limit);
[0064] Blank control group (10 group): using existing technology (NaOH strong base decomposition + TBP extraction + evaporation crystallization).
[0065] II. Experimental data and results
[0066] (I) Experimental data record table (Table 1)
[0067] Table 1, experimental group variables and results table
[0068]
[0069] (II) Weighted score calculation
[0070] Reference industry-recognized high-purity ammonium paratungstate (APT) quality standards—YS / T 231-2018 "Ammonium Paratungstate"
[0071] (I) Score basis
[0072] Purity: YS / T 231-2018 stipulates that the purity of "high-purity APT" is ≥99.99% (4N5), and the total amount of impurities is ≤0.01%; the industry requires the purity of electronic-grade APT to be ≥99.995% (5N).
[0073] Scoring rules: 99.99% as the benchmark for 60 points, each 0.001% increase in purity adds 10 points, with a maximum of 100 points (i.e., purity ≥99.994% gets 100 points).
[0074] Crystal particle size D50: High-end applications (such as ultra-fine tungsten powder preparation) require D50 = 30-50 μm (good particle size uniformity, avoiding excessive agglomeration or excessive difficulty in sintering).
[0075] Scoring rules: 30 μm as the optimal (100 points), 50 μm as the passing line (60 points), each deviation of 1 μm deducts 2 points (e.g., D50 = 40 μm, score = 100-(40-30) x 2 = 80 points; <30 μm or >50 μm is scored based on 50 μm).
[0076] Moisture content: YS / T 231-2018 requires "first-grade APT moisture ≤0.5%", and electronic-grade APT requires moisture ≤0.4%.
[0077] Scoring rules: 0.3% as the optimal (100 points), 0.5% as the passing line (60 points), each 0.1% increase in moisture deducts 20 points (e.g., moisture = 0.4%, score = 100-(0.4-0.3) / 0.1 x 20 = 80 points; >0.5% cannot score).
[0078] Based on the standard (YS / T 231-2018 and industry high-end application requirements), the comprehensive scores (81.63-93.74) of the conventional groups (1-5 groups) were significantly higher than those of the over-limit control groups (38.00-60.09) and the blank control group (18.00), verifying that when the mass fraction of ammonium carbonate was 10-12 parts, the ionic liquid concentration was 0.5-1.0 mol / L, and the ultrasonic power was 300-500 W, the product purity, particle size, and moisture performance all met the high-end APT standard, and the comprehensive performance was optimal. Among them, the third group (ammonium carbonate 11.5 parts, ionic liquid 0.8 mol / L, ultrasonic power 450 W) had the highest comprehensive score (93.74), further proving the scientificity of the parameter limitation range and the technical advantage of the process.
[0079] Based on the above experimental results, the comprehensive performance of the conventional groups in purity, crystal particle size, and moisture control was significantly better than that of the over-limit control groups and the blank control group. This difference not only reflects the effectiveness of process parameter optimization, but also stems from the synergistic mechanism at the molecular level. To better understand the regulation of parameter range on performance, the following analyzes the deep-seated reasons for the performance trend from a microscopic perspective, combined with the molecular interactions in the green ammonia decomposition, ionic liquid purification, and ultrasonic crystallization processes.
[0080] In the green ammonia decomposition link, the mass fraction of ammonium carbonate (10-12) regulates the destruction efficiency of the tungsten ore lattice by affecting the CO3 2- concentration in the solution. From a molecular perspective, CO3 2- as a weak alkaline group, can combine with Ca 2+ in the CaWO4 lattice of scheelite to form CaCO3 precipitate (solubility product Ksp = 2.8 x 10 -9 ), releasing WO4 2- into the solution. When the mass fraction of ammonium carbonate is less than 10 parts, the CO3 2- concentration is insufficient, and the combination ability with Ca 2+ is weakened, leading to incomplete decomposition of tungsten ore, resulting in a decrease in WO3 concentration in the crude liquid and an increase in subsequent purification load. When the mass fraction is higher than 12 parts, excessive CO3 2- competes with WO4 2- for active sites on the ore powder surface, forming (NH4)2CO3·(NH4)2WO4 complex salt, which actually inhibits the dissolution of WO4 2- . This is the molecular reason for the decrease in purity and dissolution efficiency in over-limit control groups 6 and 7.
[0081] In the ionic liquid deep purification link, the ionic liquid concentration (0.5-1.0 mol / L) regulates the impurity removal effect by affecting the number of active sites. The anion DEP -Containing a phosphate ester group (-P=O), its oxygen atom's lone pair electrons can interact with WO4. 2- The W atoms form coordinate bonds (O→W coordination), while simultaneously repelling impurity anions such as P, As, and Si (because the coordination energy of impurity ions with -P=O is lower than that of WO4). 2- When the concentration of the ionic liquid is below 0.5 mol / L, DEP - Insufficient active sites for WO4 2- The extraction capacity decreased, and the co-extraction rate of impurities increased (e.g., the content of P and As in the control group 8 increased to 0.15 g / L). When the concentration was higher than 1.0 mol / L, ionic liquid molecules were prone to form aggregates through the π-π stacking of imidazole rings, which led to the encapsulation of the -P=O active site and a decrease in selectivity. This explains why the purity of the control group 9 did not improve further.
[0082] In the ultrasonic-assisted cooling crystallization process, the ultrasonic power (300-500W) regulates the nucleation and growth of APT molecules through cavitation. The localized high temperature and pressure generated by ultrasonic cavitation (instantaneous temperature can reach 5000K, pressure exceeds 100MPa) disrupts the supersaturated state of the solution, promoting the formation and growth of APT molecules ((NH4)2). 10 H2(W2O7)6·H2O) oriented arrangement. When the power is below 300W, the cavitation effect is insufficient, and the supersaturated solution is difficult to break, and APT molecules are prone to disorderly aggregation to form large particles (e.g., D50 = 52.83μm in the control group 6). When the power is above 500W, the shock wave generated by the collapse of cavitation bubbles is too strong, which will cause the formed APT crystals to break, produce fine microcrystals, and increase the surface adsorption of water (e.g., the water content in the control group 7 rises to 0.52%). At a power of 300-500W, the cavitation effect can precisely control the nucleation rate and crystal growth rate, so that APT molecules grow oriented along the
[001] crystal plane to form crystals with uniform particle size (D50 = 30-50μm) and smooth surface, reducing the water adsorption sites.
[0083] In summary, the conventional group achieved comprehensive optimization of purity, particle size, and moisture content through the synergistic regulation of the "decomposition-coordination-nucleation" mechanism at the molecular level. In contrast, the out-of-limit control group experienced a decline in performance due to molecular imbalance caused by parameter deviations. This further verifies the scientific validity of the process parameter range and the technical advantages of this process at the molecular regulation level.
[0084] Exemplary Description
[0085] To faithfully reflect the formula's fluctuation range and facilitate experimental weighing, the percentage range will be directly converted into "mass parts" in the following text. That is, only the relative proportions between components are retained, and the total amount is no longer restricted to 100%. Thus, samples can be freely prepared within the specified parts range without additional correction.
[0086] Example 1
[0087] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0088] (1) Tungsten ore pretreatment: The scheelite concentrate with WO3 grade of 65% is crushed to a particle size of 3 mm by a jaw crusher, and then ground by a ball mill at a speed of 320 r / min, a medium ball diameter of Φ25 mm, a ball-to-material ratio of 5:1, and a grinding time of 1.8 h. The undersize (-200 mesh) accounts for 92% and is used as needed.
[0089] (2) Green ammonia decomposition: The pretreated tungsten ore powder is mixed with a leaching agent at a liquid-to-solid ratio of 5:1 mL / g in a porcelain reaction kettle. The leaching agent is composed of 10.0 parts of ammonium carbonate, 6.5 parts of ammonia water, and 73.5 parts of deionized water. The reaction temperature is controlled at 70°C, the stirring speed is 400 r / min, the reaction time is 3 h, and the pH is adjusted to 10.0. After the reaction, plate and frame filtration (filter cloth pore size 0.45 μm) is performed to obtain a crude tungsten acid ammonium solution with a WO3 concentration of 100 g / L.
[0090] (3) Deep purification of ionic liquid: The crude tungsten acid ammonium solution is extracted using 1-octyl-3-methyl imidazole diethyl phosphate salt ionic liquid (dissolved in sulfonated kerosene) with an ionic liquid concentration of 0.5 mol / L, a phase ratio O / A = 1:4, a temperature of 28°C, a stirring speed of 250 r / min, a mixing time of 18 min, and a clarification time of 35 min. Then, it is washed with 0.8 wt% ammonium carbonate solution (phase ratio O / A = 8:1) and stripped with 1.5 wt% ammonia solution (phase ratio O / A = 1:1, stripping time 23 min) to obtain a loaded aqueous phase (impurities P, As, Si content 0.08 g / L) with a WO3 concentration of 165 g / L.
[0091] (4) Ultrasonic-assisted cooling crystallization: The loaded aqueous phase is filtered through a 0.22 μm precision filter, 0.8 parts (based on the mass of WO3) of nano APT seed crystals (particle size 8 μm) are added, and the mixture is placed in a jacketed crystallization kettle with a stirring speed of 250 r / min, an ultrasonic frequency of 25 kHz, and an ultrasonic power of 300 W (intermittent mode: on for 5 min, off for 5 min, and on for 5 min in a cycle). The temperature is lowered to 23°C at a rate of 6°C / h, and the crystallization time is 5 h. Centrifugal filtration is performed (speed 3500 r / min, time 18 min), and the filter cake is washed twice with deionized water. The washing water is reused in step (2).
[0092] (5) mother liquor recycling: the mother liquor of crystallization is sent into a vacuum distillation column, the vacuum degree is 0.085 MPa, the temperature is 65 DEG C, ammonia gas is evaporated and condensed to obtain 18wt% ammonia water, which is returned to step (2); the residue at the bottom of the column is adsorbed by D401 chelating resin (flow rate 1.5 BV / h), and 2.5wt% ammonia water solution is eluted (flow rate 0.8 BV / h), and the eluate is returned to step (3); the CO2 generated by ammonia evaporation is introduced into a carbonation reactor (temperature 35 DEG C, pressure 0.25 MPa, reaction time 2.5 h, CO2 flow rate 0.6 L / min), to generate 11wt% ammonium carbonate solution, which is returned to step (2);
[0093] (6) ammonium paratungstate drying: the crystallization product is placed in a vacuum drying oven, dried at 60 DEG C for 1 h, 80 DEG C for 1 h, and 100 DEG C for 1 h, the vacuum degree is 0.075 MPa, and the ammonium paratungstate product is obtained after cooling.
[0094] The ammonium paratungstate product prepared in this example has a purity of 99.995%, a crystal particle size D50 = 48.62 μm, and a moisture content of 0.48%.
[0095] Example Two
[0096] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0097] (1) tungsten ore pretreatment: the same as example one;
[0098] (2) green ammonia decomposition: the mass fraction of ammonium carbonate in the leaching agent is 11.0 parts, the mass fraction of ammonia water is 6.5 parts, the mass fraction of deionized water is 72.5 parts, the ionic liquid concentration in the ionic liquid deep purification is 0.7 mol / L, the ultrasonic power in the ultrasonic assisted cooling crystallization is 400 W, and the rest of the parameters are the same as example one;
[0099] (3) ionic liquid deep purification: the same as example one;
[0100] (4) ultrasonic assisted cooling crystallization: the same as example one;
[0101] (5) mother liquor recycling: the same as example one;
[0102] (6) ammonium paratungstate drying: the same as example one.
[0103] The ammonium paratungstate product prepared in this example has a purity of 99.996%, a crystal particle size D50 = 42.35 μm, and a moisture content of 0.42%.
[0104] Example Three
[0105] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0106] (1) tungsten ore pretreatment: same as example one;
[0107] (2) green ammonia decomposition: in the leaching agent, ammonium carbonate 11.5 parts by mass, ammonia 6.5 parts, deionized water 72.0 parts, ionic liquid concentration 0.8 mol / L in ionic liquid deep purification, ultrasonic power 450W in ultrasonic assisted cooling crystallization, the rest of the parameters are the same as example one;
[0108] (3) ionic liquid deep purification: same as example one;
[0109] (4) ultrasonic assisted cooling crystallization: same as example one;
[0110] (5) mother liquor recycling: same as example one;
[0111] (6) ammonium paratungstate drying: same as example one.
[0112] The ammonium paratungstate product prepared in this example has a purity of 99.998%, a crystal particle size D50 = 38.76 μm, and a moisture content of 0.35%.
[0113] Example four
[0114] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0115] (1) tungsten ore pretreatment: same as example one;
[0116] (2) green ammonia decomposition: in the leaching agent, ammonium carbonate 12.0 parts by mass, ammonia 6.5 parts, deionized water 71.5 parts, ionic liquid concentration 1.0 mol / L in ionic liquid deep purification, ultrasonic power 500W in ultrasonic assisted cooling crystallization, the rest of the parameters are the same as example one;
[0117] (3) ionic liquid deep purification: same as example one;
[0118] (4) ultrasonic assisted cooling crystallization: same as example one;
[0119] (5) mother liquor recycling: same as example one;
[0120] (6) ammonium paratungstate drying: same as example one.
[0121] The ammonium paratungstate product prepared in this example has a purity of 99.996%, a crystal particle size D50 = 45.18 μm, and a moisture content of 0.40%.
[0122] Example five
[0123] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0124] (1) Tungsten ore pretreatment: same as example one;
[0125] (2) Green ammonia decomposition: 10.5 parts by mass of ammonium carbonate, 6.5 parts of ammonia water, 73.0 parts of deionized water in the leaching agent, 0.6 mol / L of ionic liquid concentration in the ionic liquid deep purification, 350 W of ultrasonic power in the ultrasonic-assisted cooling crystallization, and the remaining parameters are the same as those in example one;
[0126] (3) Ionic liquid deep purification: same as example one;
[0127] (4) Ultrasonic-assisted cooling crystallization: same as example one;
[0128] (5) Mother liquor recycling: same as example one;
[0129] (6) Ammonium paratungstate drying: same as example one.
[0130] The ammonium paratungstate product prepared in this example has a purity of 99.995%, a crystal particle size D50 = 46.21 μm, and a moisture content of 0.45%.
[0131] Example six (out-of-limit control group)
[0132] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0133] (1) Tungsten ore pretreatment: same as example one;
[0134] (2) Green ammonia decomposition: 8.0 parts by mass of ammonium carbonate (lower than the limited range), 6.5 parts of ammonia water, 75.5 parts of deionized water in the leaching agent, and the remaining parameters are the same as those in example one;
[0135] (3) Ionic liquid deep purification: same as example one;
[0136] (4) Ultrasonic-assisted cooling crystallization: same as example one;
[0137] (5) Mother liquor recycling: same as example one;
[0138] (6) Ammonium paratungstate drying: same as example one.
[0139] The ammonium paratungstate product prepared in this example has a purity of 99.990%, a crystal particle size D50 = 52.83 μm, and a moisture content of 0.55%.
[0140] Example seven (out-of-limit control group)
[0141] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0142] (1) tungsten ore pretreatment: same as example one;
[0143] (2) green ammonia decomposition: 14.0 parts by mass of ammonium carbonate (higher than the limited range), 6.5 parts of ammonia water, 79.5 parts of deionized water in the leaching agent, and the rest of the parameters are the same as example one;
[0144] (3) ionic liquid deep purification: same as example one;
[0145] (4) ultrasonic-assisted cooling crystallization: same as example one;
[0146] (5) mother liquor recycling: same as example one;
[0147] (6) ammonium paratungstate drying: same as example one.
[0148] The ammonium paratungstate product prepared in this example has a purity of 99.991%, a crystal particle size D50 = 50.17 μm, and a moisture content of 0.52%.
[0149] Example eight (out-of-limit control group)
[0150] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0151] (1) tungsten ore pretreatment: same as example one;
[0152] (2) green ammonia decomposition: same as example one;
[0153] (3) ionic liquid deep purification: ionic liquid concentration 0.3 mol / L (lower than the limited range), and the rest of the parameters are the same as example one;
[0154] (4) ultrasonic-assisted cooling crystallization: same as example one;
[0155] (5) mother liquor recycling: same as example one;
[0156] (6) ammonium paratungstate drying: same as example one.
[0157] The ammonium paratungstate product prepared in this example has a purity of 99.988%, a crystal particle size D50 = 55.32 μm, and a moisture content of 0.58%.
[0158] Example nine (out-of-limit control group)
[0159] A method for green preparation of high-purity ammonium paratungstate from tungsten ore, comprising the following steps:
[0160] (1) tungsten ore pretreatment: same as example one;
[0161] (2) green ammonia decomposition: same as example one;
[0162] (3) Ionic liquid deep purification: Ionic liquid concentration 1.2 mol / L (higher than the defined range), the rest of the parameters are the same as Example One;
[0163] (4) Ultrasonic assisted cooling crystallization: The same as Example One;
[0164] (5) Mother liquor recycling: The same as Example One;
[0165] (6) Ammonium paratungstate drying: The same as Example One.
[0166] The purity of the ammonium paratungstate product prepared in this example is 99.990%, the crystal particle size D50 = 49.85 μm, and the moisture content is 0.50%.
[0167] Example Ten (blank control group)
[0168] A method for preparing ammonium paratungstate from tungsten ore (prior art) includes the following steps:
[0169] (1) Tungsten ore pretreatment: The same as Example One;
[0170] (2) NaOH strong base decomposition: Mix tungsten ore powder with 20wt% NaOH solution at a liquid-solid ratio of 4:1 mL / g, calcine in a stainless steel reactor at 150°C for 2h, then water leach (80°C, stirring for 2h), and filter to obtain a crude sodium tungstate solution;
[0171] (3) TBP extraction purification: Use 20vol% TBP-sulfonated kerosene solution for extraction, phase ratio O / A = 1:3, temperature 40°C, back extraction with 5wt% HCl solution (phase ratio O / A = 1:2), and obtain pure tungstic acid solution;
[0172] (4) Evaporation crystallization: Add ammonia water to the pure tungstic acid solution to adjust the pH to 8.5, evaporate and concentrate (100°C, normal pressure) to a solution density of 1.3 g / cm 3 , cool to 30°C to crystallize, and centrifuge and filter to obtain APT wet crystals;
[0173] (5) Drying: Dry the wet crystals in an oven at 120°C for 3h to obtain ammonium paratungstate product.
[0174] The purity of the ammonium paratungstate product prepared in this example is 99.980%, the crystal particle size D50 = 62.54 μm, and the moisture content is 0.65%.
[0175] Specific working process
[0176] Please refer to Figure 1, tungsten ore is crushed and ground to -200 mesh, accounting for ≥90%, the undersize is mixed with a leaching agent composed of ammonium carbonate, ammonia and deionized water, in a weak alkaline environment, CO3 2- of ammonium carbonate combines with metal cations (such as Ca 2+ , Fe 2+ , Mn 2+ ) in the tungsten ore lattice to form insoluble carbonate precipitates, releasing WO4 2- into the solution to form a crude ammonium tungstate solution, after solid-liquid separation, the filter residue is sent to the tailings recovery, and the filtrate enters the purification process.
[0177] The crude ammonium tungstate solution is contacted with a functionalized phosphate-based ionic liquid, the active groups of the phosphate-based ionic liquid form coordination bonds with WO4 2- through the oxygen atom lone pair electrons, realizing selective extraction of tungsten, while excluding impurity anions such as P, As, Si, etc.; the tungsten-loaded ionic liquid is washed to remove entrained impurities, and then contacted with an ammonia solution, WO4 2- is back-extracted from the ionic liquid into the aqueous phase to obtain a high-purity ammonium tungstate solution, and the ionic liquid is regenerated and recycled.
[0178] The high-purity ammonium tungstate solution is cooled and crystallized under the action of an ultrasonic field, the local high temperature and high pressure generated by ultrasonic cavitation destroys the supersaturation state of the solution, promotes the directional arrangement and nucleation of APT molecules, and reduces agglomeration by inducing crystal growth of nanoscale APT seeds; after crystallization is completed, solid-liquid separation is performed to obtain APT wet crystals, the filter cake is washed with deionized water to remove surface free ammonium ions, and the washing water is returned to the leaching process.
[0179] The crystallization mother liquor is sent to a vacuum distillation column, the ammonia gas evaporated is condensed to form an ammonia water solution which is returned to the leaching process; the carbon dioxide gas generated by distillation is introduced into a carbonation reactor to react with deionized water to generate an ammonium carbonate solution which is also returned to the leaching process as a leaching agent; the residue at the bottom of the distillation column is adsorbed by a chelating resin to remove residual WO3, and after adsorption saturation, the chelating resin is eluted with an ammonia solution, and the eluate is returned to the extraction process.
[0180] The APT wet crystals are dried in stages, and water is removed under low-temperature, medium-temperature and high-temperature conditions, respectively, and the drying temperature is reduced by vacuum environment to avoid oxidation of the crystals, and finally ammonium paratungstate product is obtained.
[0181] The technical features described in the above examples can be combined in any way, and to make the description concise, not all possible combinations of the technical features in the above examples are described, however, as long as the combinations of the technical features do not exist contradictory, they should be considered as the scope of the description.
Claims
1. A process for green production of high purity ammonium paratungstate from tungsten ore, characterized by: The method comprises the following steps: (1) tungsten ore pretreatment: crushing and grinding the tungsten ore to -200 mesh, with a proportion of ≥90%; (2) green ammonia decomposition: mixing and reacting the pretreated tungsten ore with a leaching agent, the leaching agent being composed of 10-12 parts of ammonium carbonate, 5-8 parts of ammonia water and 70-80 parts of deionized water, the reaction temperature being 60-80℃, the stirring rate being 300-500r / min, the reaction time being 2-4h, and the liquid-solid ratio being 4:1-6:1 mL / g; (3) deep purification of ionic liquid: extracting the crude ammonium tungstate solution of step (2) with a functionalized phosphate-based ionic liquid, the concentration of the functionalized phosphate-based ionic liquid being 0.5-1.0 mol / L, the extraction phase ratio O / A being 1:3-1:5, and the temperature being 25-30℃; (4) ultrasonic-assisted cooling crystallization: cooling and crystallizing the extracted ammonium tungstate solution under an ultrasonic field, the ultrasonic frequency being 20-30 kHz, the power being 300-500W, the cooling rate being 5-8℃ / h, and the final temperature being 20-25℃; (5) recycling of mother liquor: recycling the crystallization mother liquor through ammonia evaporation under reduced pressure, carbonization reaction and tungsten residue recovery, the ammonia evaporation vacuum degree being 0.08-0.09 MPa, the temperature being 60-70℃, and the CO2 flow rate being 0.5-1.0 L / min in the carbonization reaction; (6) drying of ammonium paratungstate: drying the crystallization product at 80-100℃ and a vacuum degree of 0.07-0.08 MPa for 2-3h.
2. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 1, wherein: The tungsten ore in step (1) is scheelite or wolframite concentrate with a WO3 grade of ≥65%; the crushing is performed by a jaw crusher, and the particle size after crushing is ≤3mm; the grinding is performed by a ball mill at a rotating speed of 300-350r / min, a medium ball diameter of Φ20-30mm, a ball-to-material ratio of 5:1, a grinding time of 1.5-2h, and a 200-mesh standard sieve for screening, with the oversize returned to the ball mill.
3. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 1, wherein: The pH of the green ammonia decomposition in step (2) is controlled at 9.5-10.5, and the reaction equipment is a enamel reaction kettle; after the reaction, solid-liquid separation is performed by plate-and-frame filtration with a filter cloth pore size of 0.45μm, the filter residue being calcium carbonate or iron-manganese carbonate and being sent to tailings recovery, and the filtrate being a crude ammonium tungstate solution with a WO3 concentration of 80-120g / L.
4. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 1, wherein: The functionalized phosphate-based ionic liquid in step (3) is 1-octyl-3-methyl imidazole diethyl phosphate salt, and the diluent is sulfonated kerosene; the stirring rate in the extraction process is 200-300r / min, the mixing time is 15-20min, and the clarification time is 30-40min; after 50 cycles of extraction and back extraction, the extraction capacity decreases by ≤3%.
5. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 4 wherein: Step (3) further comprises washing and back extraction: the washing agent is an ammonium carbonate solution with a concentration of 0.5-1.0wt%, and the phase ratio O / A is 5:1-10:1; the back extraction agent is an ammonia water solution with a concentration of 1-2wt%, and the phase ratio O / A is 1:1, and the back extraction time is 20-25min.
6. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 1, wherein: The ammonium tungstate solution is subjected to 0.22μm precision filtration before the ultrasonic-assisted cooling crystallization in step (4). The nanometer ammonium paratungstate seed is added in the crystallization process, the adding amount is 0.5-1.0wt% of WO3 mass in the solution, the stirring rate is 200-300r / min, the crystallization time is 4-6h; the ultrasonic is intermittent mode, open 5min, close 5min, open 5min cycle.
7. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 1, wherein: The solid-liquid separation after crystallization in step (4) adopts centrifugal filtration, the rotating speed is 3000-4000r / min, the time is 15-20min; the filter cake is washed with deionized water for 2-3 times, and the washing water is reused to step (2) as leaching agent.
8. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 1, wherein: After the ammonia is reduced and evaporated in step (5), the ammonia gas is condensed to obtain ammonia water with a concentration of 15-20wt%, which is returned to step (2) as leaching agent; the carbonization reaction temperature is 30-40℃, the pressure is 0.2-0.3MPa, the reaction time is 2-3h, and the ammonium carbonate solution with a concentration of 10-12wt% is generated and returned to step (2) as leaching agent.
9. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 1, wherein: The D401 type chelating resin is used for the tungsten residue recovery in step (5); the residual liquid flow rate is 1-2BV / h, the breakthrough point is controlled to be WO3 concentration of the effluent>0.1g / L; the eluent is ammonia water solution with a concentration of 2-3wt%, the flow rate is 0.5-1BV / h, and the eluate is returned to step (3) for extraction.
10. A process for the green production of high purity ammonium paratungstate from tungsten ores as claimed in claim 1, wherein: The ammonium paratungstate drying in step (6) is segmented drying: drying at 60℃ for 0.5-1h, drying at 80℃ for 0.5-1h, and drying at 100℃ for 0.5-1h; after drying, nitrogen is introduced to cool to room temperature, the product moisture is≤0.5%, and the crystal particle size D50=30-50μm.